2013
DOI: 10.1177/1471301213501821
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers’ perspectives on dementia-related dressing difficulties at home: The preservation of self model

Abstract: Alzheimer's caregiving literature acknowledges dressing as a major daily stressor but research on this topic is negligible. A qualitative grounded theory approach was used to explore Alzheimer's family caregivers' perspectives about issues that arise when their family members lose the ability to dress independently. Three focus groups and seven individual interviews were conducted and audio recorded with 25 information rich caregivers. Constant comparative analyses and coding of the transcripts identified six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
(27 reference statements)
2
27
0
2
Order By: Relevance
“…Researchers such as Bowers and Mahoney et al. have indicated that the phenomenon of family care partners’ concern related to the value of dignity is persistent. Proceeding from the theoretical contributions of Nordenfelt and Stevens et al.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Researchers such as Bowers and Mahoney et al. have indicated that the phenomenon of family care partners’ concern related to the value of dignity is persistent. Proceeding from the theoretical contributions of Nordenfelt and Stevens et al.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The numerous dressing and interpersonal challenges experienced in family caregiving as well as extensive details on the qualitative methodology have been reported previously 9 . This paper uniquely reports the caregivers’ reactions to the proposed technology and their recommendations to improve usability for PWD.…”
Section: Methodsmentioning
confidence: 99%
“…Direct aids to help caregivers manage dressing problems also are limited. Alzheimer’s caregivers complain that commercially available dressing aids such as button-hooks and stocking pull-ons are designed for persons with physical disabilities and are too complex and confusing to those with dementia 9 .…”
mentioning
confidence: 99%
“…Una mayor frecuencia de cuidado se relaciona con más sobrecarga y a su vez, más sobrecarga se relaciona con menos satisfacción". Apoyan tan afirmación autores como Fauth, Femia & Zarit (2016), Mahoney, LaRose & Mahoney (2015), o Prick, de Lange, Twisk & Pot, (2015).…”
Section: Modelo De Ecuaciones Estructuralesunclassified
“…Por el contrario, la demanda de cuidados conduce a factores de riesgo como la sobrecarga o el aislamiento social, los cuales deben ser analizados (Mahoney, LaRose & Mahoney (2015) El aislamiento se refiere a la condición de no tener vínculos con los demás, pudiendo desembocar en una desconexión social del sistema (Ferreira Alves, Magalhaes, Viola & Simoes, 2014). Consecuentemente, se ha encontrado una fuerte asociación entre el aislamiento social y la depresión, independientemente de la soledad, incluyendo además resultados negativos como la mortalidad y el deterioro cognitivo (Medvene et al, 2015).…”
unclassified